Strategi Branding Pengembangan Industri Pariwisata 4.0 Melalui Kompetitif Multimedia di Era Digital - Isdarmanto Isdarmanto (Diploma Travel Business, Faculty of Social and Political Science, Jember University, 2020)
Role of information technology in the development of tourism in the current era of globalization has a very important role in particular the marketing program of tourism branding products from every region throughout Indonesia. Dissemination of information uploaded in the internet media from the growth of tourist destinations and regional tourism attractions is easily spread throughout the world. Through internet video, images and news can quickly and effectively be accepted by every individual. Every company organization by accessing internet media can take advantage of their business opportunities, through various features and programs that are applied in multimedia, giving many choices which are effectively used. Business marketing branding can be uploaded and promoted faster according to market share. The tourism industry 4.0 is a challenge for every country in the world to compete in increasing the role of human resources in the tourism industry through the digital era. The more digital the professional, the more digital the more global. This study uses qualitative research that enables and understands the problem of deepening. The purpose of this study is to determine the multimedia implications of communication technology in building branding as a major factor synchronizing the development of the Tourism industry 4.0. The development of branding through multimedia programs will be very effective throughout the world in the concept of institutional or corporate positioning and must be managed properly.